Author Correction: Imaging and clinical data archive for head and neck squamous cell carcinoma patients treated with radiotherapy. Issue 1 (December 2018) - Grossberg, Aaron; Mohamed, Abdallah; Elhalawani, Hesham; Bennett, William; Smith, Kirk; Nolan, Tracy; Williams, Bowman; Chamchod, Sasikarn; Heukelom, Jolien; Kantor, Michael; Browne, Theodora; Hutcheson, Katherine; et al.
In the original version of the Data Descriptor the surname of author Hesham Elhalawani was misspelled. This has now been corrected in the HTML and PDF versions.